Development of Smart Shoes Using Piezoelectric Material - Abdul Rashid, Affa Rozana; Md Sarif, Nur Insyierah; Ismail, Khadijah (Malaysian Journal of Science Health & Technology, 2021)
The consumption of low-power electronic devices has increased rapidly, where almost all applications use power electronic devices. Due to the increase in portable electronic devices’ energy consumption, the piezoelectric material is proposed as one of the alternatives of the significant alternative energy harvesters. This study aims to create a prototype of “Smart Shoes” that can generate electricity using three different designs embedded by piezoelectric materials: ceramic, polymer, and a combination of both piezoelectric materials. The basic principle for smart shoes’ prototype is based on the pressure produced from piezoelectric material converted from mechanical energy into electrical energy. The piezoelectric material was placed into the shoes’ sole, and the energy produced due to the pressure from walking, jogging, and jumping was measured. The energy generated was stored in a capacitor as piezoelectric material produced a small scale of energy harvesting. The highest energy generated was produced by ceramic piezoelectric material under jumping activity, which was 1.804 mJ. Polymer piezoelectric material produced very minimal energy, which was 55.618 mJ. The combination of both piezoelectric materials produced energy, which was 1.805 mJ from jumping activity.